Electrical conductive epoxy composites containing cilia-like powders fabricated by mechanical milling - Cho, Minkyung; Choi, Hyunjoo; Aslam, Muhammad; Shin, Jaehyuck; Bae, Donghyun (Metals and materials international, 2010)
Electrically conductive epoxy composites were developed by adding cilia-like powders produced by dispersing multi-walled carbon nanotubes (MWNTs) on copper particles via mechanical milling. During the milling process, the MWNTs were gradually dispersed and partially embedded in the copper particles, producing cilialike powders that enhanced the electrical conductivity of the epoxy composites. With further milling, however, excessive embedding of the MWNTs in the copper particles resulted in decreased electrical conductivity. Electrical conductivity of the epoxy composites containing 24 vol.% of the cilia-like powders (milled for 1 h) was remarkably enhanced up to 15 S/cm.